The Effectiveness of Sexual Reproductive Health (SRH) Programme Among Adolescents in Cheras, Malaysia - AZ, Zaitul Akmal; N, Salmah; Ismail, ND; MN, Muhammad Akmal; K, Khairatul Nainey (International Journal of Human and Health Sciences (IJHHS), 2021)
Introduction: In Malaysia, the rate of adolescents involved in sexual activities has increased and starts at an earlier age. Data from NHMS 2017 showed that 7.3% among surveyed 13 to 17 years-old adolescents have already had sex. The rate of teenage pregnancies is also increasing at 3.7-3.9% between the years 2009 until 2011. Therefore, an effective SRH Programme should be conducted in schools to equip them with adequate knowledge regarding this subject. Methods: A cross-sectional questionnaire survey was conducted among 145 randomly selected secondary school students aged 13 to 15 years old, attending the SRH Programme in a secondary school in Cheras, Selangor, Malaysia. The objective of this programme is to deliver knowledge and promote awareness among adolescents regarding SRH. The programme consists of intervention using adolescent-friendly module and games. A pre- and post-test were given to the participants to evaluate the effectiveness of the programme using the validated SRH questionnaire (Malay version). The questionnaire consists of fourteen and six items for knowledge and attitude, respectively. Results: The result showed an increase in the mean knowledge score (±SD) after the SRH Programme at the school from 7.25 ± 2.44 for pre-test to 9.70 ± 3.17 for post-test. The mean difference in pre- and post-test was 2.45 (95% CI: 2.02, 2.87) and was statistically significant (p<0.001). In terms of attitudes, the majority of the students felt that they have enough knowledge to make a gooddecision regarding sexual reproductive health issues after the SRH programme. However, there was only a small increment with regards to their attitudes on assertiveness. Conclusion: This study demonstrated an increase in the level of knowledge among adolescents in Cheras after the SRH programme using the adolescent-friendly module and games. However, there is no significant change in attitude among adolescents regarding SRH.Future SRH programmes need to be done regularly to instil positive attitudes among adolescents in dealing withsexual reproductive dilemmas. International Journal of Human and Health Sciences Supplementary Issue: 2021 Page: S20